Achieving sustainable agriculture in Nigeria: A land-use policy perspective - Idris, Nasiru Medugu (2006)
Agriculture has changed dramatically, especially since the end of World War II. Food and fiber productivity soared due to new technologies, mechanization, increased chemical use, specialization and government policies that favored maximizing production. Sustainable agriculture refers to the ability of a farm to produce perpetually base on long-term effects of various practices on soil properties and processes essential for crop productivity, and the long-term availability of inputs. It integrates three main goals: environmental stewardship, farm profitability, and prosperous farming communities. These goals have been defined by various disciplines and may be looked at from the vantage point of the farmer or the consumer. This paper is an effort to identify the ideas, practices and policies that constitute our concept of sustainable agriculture.